CRITICAL REVIEW IN ENHANCING EMERGENCY HEALTHCARE DELIVERY THROUGH INTEGRATION OF NURSING AND TECHNICIAN ROLES - 1Tareq Husain kursan Alyami, 2Ali MohmmedHamad Alqirad, 3Mahdi Awad Mahdi Almakayik, 4Saud Daghman Hussain Al Daghman, 5Yousef Abdullah Ali Al Jamish, 6Fayez Mohammed Ali Al Asloom, 7Mohammed Abdullah Mead Alhamamah, 8Ali Mohammed TayyibShamlan, (Chelonian Research Foundation, 2022)
The integration of nursing and technician roles in emergency healthcare aims to bolster efficiency and effectiveness in addressing urgent medical needs. This literature analyzes the writing on this integration, taking a closer look at its results, challenges, and benefits. Examining different study’s, strategies, and discoveries uncovers the current field of emergencymedical room and the vital part of integration in this field. Proposals for future inquiries and usage methodologies are also depicted. This article highlights the significance of coordination between nursing and staff as a promising approach to progressing emergency care. It also highlights the need for assistance, investigation, and collaboration to realize its full potential. Keywords: emergency healthcare, nursing, technician roles, integration, efficiency, effectiveness.